Reduced corneal endothelial cell density after toxic anterior segment syndrome (TASS) caused by inadvertent intraocular ointment migration: A case report - Mohamed Noriega, Karim; Guerra Lorenzo, Fernando; Mohamed Noriega, Jibran; Villarreal Mendez, Gerardo; Morales Wong, Fernando; Mohamed Hamsho, Jesús (2022)
Introduction and importance: Toxic anterior segment syndrome (TASS) is an acute sterile inflammation of the anterior segment which may occur after surgery. This case presents endothelial cell density (ECD) loss due to months of TASS caused by intraocular migration of ocular ointment. The chronicity of this case and the clinical consequences are rare in the literature. Case presentation: A Colombian 71-year-old man developed TASS secondary to intraocular ointment migration after uneventful cataract surgery with phacoemulsification and intraocular lens placement in the capsular bag. The main complaint for the patient was a chronic red eye, no pain or visual disturbance were reported, rheumatologic diseases were discarded. It was documented the presence of intraocular ointment in the anterior chamber, over the iris and in the anterior chamber angle. The ECD was reduced secondary to TASS and the longterm presence of ointment moving in the anterior chamber, so it had to be removed. Clinical discussion: It is important to avoid using ocular ointment after intraocular surgeries to avoid the risk of ointment migration into the anterior chamber. Intraocular ointments should be removed promptly to reduce ECD loss as documented in the present case report in which after ointment elimination ECD remains stable for 7 years. Conclusion: Topical ointments should not be used after routine cataract surgery because of the risk of intraocular ointment migration and subsequent risk of developing TASS and reduced ECD.